Effect of Internal Crisis Communication Strategies on Employee Work Performance During Covid-19 Pandemic in Level Four Hospitals in Uasin Gishu Countyect of Internal Crisis Communication Strategies on Employee Work Performance During Covid-19 Pandemic in Level Four Hospitals in Uasin Gishu County - Atieno, Rasowo Eileen (Daystar University, School of Communication, 2024)
This study aimed to establish the effect of internal crisis communication strategies on employee work performance in level four hospitals in Uasin Gishu county during the pandemic. Specifically, it examines the effects of information sharing, communication channels, and leadership communication on employee work performance in these healthcare facilities during this period. The study adopted a causal-comparative design and a mixed-method approach. Causal-comparative design identifies causal relationships between variables (Brown, 2020), while a mixed-method approach concurrently collects quantitative and qualitative data to complement and enhance findings (Creswell, 2014). Data was collected in level four hospitals in Uasin Gishu County. 287 employees and 16 section heads were sampled using a two-stage stratified sampling method. The first stage involved stratifying the study units into groups, followed by further stratification of employees. Random sampling was then used to select the final sample of section heads and employees. The research employed multiple regression analysis to determine the effect of internal crisis communication strategies on employee work performance. The study revealed that both information sharing (b=0.464, p<0.001) and communication channels (b=0.437, p<0.001) had positive and statistically significant effects on employee work performance. Conversely, leadership communication was found to have a negative but statistically non-significant impact on employee work performance (b=-0.015, p=.610). These findings indicate that in the context of the COVID-19 pandemic, internal crisis communication management within level four hospitals in Uasin Gishu County was a critical determinant of employee work performance. Effective communication channels and information sharing positively impacted employee work performance in the county. Given the findings of this study, there is a need for future research to comparatively analyze the impacts of these strategies to identify and recommend the most effective combination for optimizing internal crisis communication within organizations in different contexts.
MASTER OF ARTS in Communication
Keywords: Internal crisis communication strategies; Employee work performance; Pandemic